2013
DOI: 10.1038/ncomms2929
|View full text |Cite
|
Sign up to set email alerts
|

Catalytically active single-atom niobium in graphitic layers

Abstract: Carbides of groups IV through VI (Ti, V and Cr groups) have long been proposed as substitutes for noble metal-based electrocatalysts in polymer electrolyte fuel cells. However, their catalytic activity has been extremely limited because of the low density and stability of catalytically active sites. Here we report the excellent performance of a niobium-carbon structure for catalysing the cathodic oxygen reduction reaction. A large number of single niobium atoms and ultra small clusters trapped in graphitic lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
169
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 270 publications
(172 citation statements)
references
References 40 publications
1
169
0
Order By: Relevance
“…STEM imaging was performed using a fifth-order aberration-corrected STEM (Nion-UltraSTEM100) with a cold field emission electron source. The microscope was operated at a low accelerating voltage of 60 kV to prevent knockon damage to the sp 2 bonded carbon in graphene [45][46][47] . The achievable spatial resolution is B1.2 Å.…”
Section: Stem-eels Experimentsmentioning
confidence: 99%
“…STEM imaging was performed using a fifth-order aberration-corrected STEM (Nion-UltraSTEM100) with a cold field emission electron source. The microscope was operated at a low accelerating voltage of 60 kV to prevent knockon damage to the sp 2 bonded carbon in graphene [45][46][47] . The achievable spatial resolution is B1.2 Å.…”
Section: Stem-eels Experimentsmentioning
confidence: 99%
“…20,21 Therefore, it is essential to find appropriate substrates that may strongly pin the metal species, yet maintain their high chemical activity. To this end, experimental research has shown that oxide supports such as MgO, 20 FeO x , 19 SiO 2 22 and TiO 2 23 or graphitic layers 24 can anchor single metal atoms and hence allow synthesis of SACs by using the mass-selected soft-landing technique, improved wet chemistry methods, or atomic layer deposition methods. 19,20,24 Particularly, two-dimensional (2D) materials with a large surface area and high thermal stability, such as graphene, [25][26][27][28][29] graphyne, 30,31 MoS 2 32 and freestanding hexagonal boron nitride monolayers (h-BN), 33,34 can be used as prominent supports to host single metal atoms, which exhibit superb catalytic activity for CO oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, experimental research has shown that oxide supports such as MgO, 20 FeO x , 19 SiO 2 22 and TiO 2 23 or graphitic layers 24 can anchor single metal atoms and hence allow synthesis of SACs by using the mass-selected soft-landing technique, improved wet chemistry methods, or atomic layer deposition methods. 19,20,24 Particularly, two-dimensional (2D) materials with a large surface area and high thermal stability, such as graphene, [25][26][27][28][29] graphyne, 30,31 MoS 2 32 and freestanding hexagonal boron nitride monolayers (h-BN), 33,34 can be used as prominent supports to host single metal atoms, which exhibit superb catalytic activity for CO oxidation. [35][36][37][38] Recent experimental studies also showed that Ag supported by BN nanosheets with good thermal stability can be used as an effective catalyst for the reduction of p-nitrophenol 39,40 and the methanol oxidation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, we synthesized a ðNbþNbCÞ=C composite by a modified arc-discharge method, in which single niobium atoms can be stabilized into defective graphitic layers at high density [13]. Both theoretical and experimental studies showed the most probable atomic configuration and a significant electronic interaction between the single niobium atoms and the surrounding carbon atoms.…”
mentioning
confidence: 99%